Multilevel Approach to Evaluating the Comfort of Functional Clothing (Journal of Fiber Bioengineering and Informatics, 2008)
Research has demonstrated that sensorial clothing comfort is a complex function of materialproperties, garment design, as well as conditions of use. This paper discusses a modern holisticapproach to clothing comfort assessment that is based on a multilevel concept, advancing from theinvestigation of fabric properties to, ultimately, analysis of complete garment systems in controlledwear trials. It describes the value of the measurements made by advanced instrumented measurementsystems when used as part of comprehensive research program designed to explain human response tothe wear comfort of functional clothing and materials.